A new spesies of the cestode echeneibothrium benedeni n.sp from rhynchobatus djeddensis at panji, goa state, india - Khamkar, D D; Mote, A N (International Multidisciplinary Research Journal, 2011)
The present communication deals with the description of new species of genus Echeneibothrium benedeni n.sp. comes closer E. flexile Linton, 1890 [1] on the basis of number of loculi on each bothridium, however it differs from them in number of loculi; number of testes cirrus, position, genital, pore, and vittellaria.